UPAYA PEMERINTAH INDONESIA DALAM MELINDUNGI PEKERJA MIGRAN INDONESIA DI ARAB SAUDI SELAMA PANDEMI COVID-19 (2020-2021) - Diwananda Islamy, Kayana Violetta; Jatmika, Muhammad Indrawan (Indonesian Association for International Relations, 2024)
This research aims to explain the efforts made by the Indonesian Government to protect Indonesian Migrant Workers (IMW) in Saudi Arabia during the Covid-19 pandemic. The research method used is descriptive-qualitative to describe the phenomenon that occurs specifically and systematically. This research uses the National Interest and Securitization theory approach as the theoretical basis. The results show that the Indonesian government has made efforts to protect IMW in Saudi Arabia during the Covid-19 pc with three securitization steps, namely securitizing move, existential threat & referent object, and extraordinary measures. The Indonesian government as a securitization actor is carrying out a securitizing move, the Covid-19 virus is an existential threat, IMW in Saudi Arabia is the referent object, and the protection assistance efforts from the Indonesian government are extraordinary measures